Objective and subjective assessment of chronic disease management in General Practice. To determine the standard of care provided in the management of asthma, gout and hypothyroidism by means of a medical audit - Hobson, Biano; Rosochacki, Alexander; Kidd, Martin (Stellenbosch : University of Stellenbosch, 2015)
Thesis (MMed)--Stellenbosch University, 2015.